2012
DOI: 10.1128/jvi.00928-12
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Serotype 26 Utilizes CD46 as a Primary Cellular Receptor and Only Transiently Activates T Lymphocytes following Vaccination of Rhesus Monkeys

Abstract: The cellular receptor utilized by adenovirus serotype 26 (Ad26) has remained unclear. Here we show that Ad26 transduction is CD46-dependent and is efficiently blocked by anti-CD46 but not anti-CAR antibodies, demonstrating that Ad26 utilizes CD46 as a primary cellular receptor. Moreover, following Ad26 vaccination of rhesus monkeys, we did not observe sustained activation of peripheral or mucosal vector-specific CD4 + T lymphocytes. These data contribute to our understanding of Ad26 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 16 publications
4
62
1
Order By: Relevance
“…This increased recall response was observed in both the lymphoid and nonlymphoid tissues after challenge of recipient mice with MVA-Gag. It is well established that Ad5, Ad26, and Ad35 differ in their tropism (30) and primary cellular receptors (5,(7)(8)(9)27). A study by Kaufman et al (10) examined the transgene expression, distribution, and magnitude of Ad5 and Ad26 vectors expressing SIV Gag and observed that all vectors induced comparable magnitudes and kinetics of T cell responses in various systemic and mucosal tissues following i.m.…”
Section: Length Of Antigen Rest Between Priming and Boosting Impacts mentioning
confidence: 99%
See 1 more Smart Citation
“…This increased recall response was observed in both the lymphoid and nonlymphoid tissues after challenge of recipient mice with MVA-Gag. It is well established that Ad5, Ad26, and Ad35 differ in their tropism (30) and primary cellular receptors (5,(7)(8)(9)27). A study by Kaufman et al (10) examined the transgene expression, distribution, and magnitude of Ad5 and Ad26 vectors expressing SIV Gag and observed that all vectors induced comparable magnitudes and kinetics of T cell responses in various systemic and mucosal tissues following i.m.…”
Section: Length Of Antigen Rest Between Priming and Boosting Impacts mentioning
confidence: 99%
“…Recently, it was shown that CD46 is also the primary cellular receptor for Ad26 (9). Although CAR is expressed in humans, nonhuman primates, and mice in similar anatomical locations (5, 7), CD46 is not expressed in mice except in the testes (8).…”
mentioning
confidence: 99%
“…However, Ad26 and Ad35 vectors are substantially biologically different from Ad5 vectors in terms of tropism, cellular receptor usage, innate immune profile, and adaptive immune phenotypes (16,(27)(28)(29)(30). Moreover, we did not evaluate the effects of Ad5 vectors in the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Ad26 vector-specific CD4 ϩ and CD8 ϩ T cells were quantified in paired blood and foreskin specimens from the vaccinated and sham-immunized animals via ICS as previously described (16). Briefly, isolated PBMC and foreskin lymphocytes were incubated with or without stimulation using a pool of Ad26 hexon peptides (hexon; 6 h stimulation) or empty Ad26 vectors at a multiplicity of infection of 10 4 (Ad26; overnight stimulation).…”
Section: Animals Immunizations and Infectionmentioning
confidence: 99%
“…Like other HAdV-C serotypes, Ad6 uses the coxsackievirus and adenovirus receptor (CAR) and ␣v integrins as well as binds vitamin K-dependent clotting factors that modulate its pharmacology (reviewed in reference 10). In contrast, Ad26 is thought to bind CD46 as its primary receptor (11) and to use ␣v integrins (12) but does not appear to bind clotting factors (13). Given their lower seroprevalence and unique biological properties, both Ad6 and Ad26 are being developed as vaccine and oncolytic vectors (12,(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%